Opposition Based Genetic Algorithm with Cauchy Mutation for Function Optimization - Iqbal, M Amjad; Khan, Naveed Kazim; Jaffar, M Arfan; Ramzan, M; Baig, A Rauf (2010 International Conference on Information Science and Applications, 2010)
Evolutionary algorithms (EA) have been used in data classification and data clustering task since the advent of these algorithms. Nonlinear complex optimization problems have been the area of interest since very long time. The EA have been applied successfully on these optimization problems. The evolutionary algorithms suffer a lot due to their slow convergence rate, mainly due to evolutionary nature of these algorithms. This paper presents a new mutation scheme for opposition based genetic algorithms (OGA-CM). This scheme tunes the population during evolutionary process effectively by using Cauchy Mutation (CM). The performance of the algorithm is tested over suit of 5 functions. Opposition based Genetic Algorithm (OGA) is used as competitor algorithm to compare the results of the proposed algorithm. The results show that the proposed method outperforms GA and OGA for most of the test functions.